تسليم البضائع وفقا لعقد النقل البحري - أعراب, كميلة (جامعة الوادي University of Eloued, 2019)
يحتل نقل البضائع عن طريق البحر منذ زمن طويل، وحتى عصرنا الحالي أهمية بالغة باعتباره همزة وصل ووسيلة التقاء واتصال شعوبها، لذا أصبح عقد النقل البحري للبضائع من أحد المقومات الاقتصادية للدول البحرية خاصة منها الجزائر. يرتب عقد النقل البحري للبضائع التزام أساسي على عاتق الناقل وهو تسليم البضائع للمرسل إليه في المكان والزمان المتفق عليهما أو المعقول، وبهذا ينتهي تنفيذ عقد النقل البحري. إلا أنه في بعض الحالات لا يتمكن الناقل من تنفيذ عقد النقل البحري نتيجة التأخير في تسليم البضائع في الزمان المتفق عليه أو في الزمان المعقول لذلك يتم مساءلته في حالة إثبات المرسل إليه أن ضررا أصابه جراء التأخر في تسليم البضائع له. The long-term transport of goods by sea has been of great importance as a link and means of communication and communication between its peoples. The contract of maritime transport of goods has become one of the economic assets of the maritime countries, especially Algeria. The contract for the carriage of goods by sea arranges a fundamental obligation on the carrier to deliver the goods to the consignee at the agreed or reasonable time and place, thereby ending the implementation of the contract of maritime carriage. In some cases, however, the carrier is unable to perform the maritime carriage contract as a result of the delay in the delivery of the goods at the agreed time or in a reasonable time, so that it is held accountable if the consignee proves that the goods have been damaged.
Keywords: عقد النقل البحري، سند الشحن، البضائع، الناقل